Protein Sel Tunggal Sebagai Substitusi Tepung Ikan Dalam Pakan Juvenil Ikan Mas (Cyprinus carpio) - Nur Bambang Priyo Utomo; Ing Mokoginta; Erwin Suwendi (Jurnal Perikanan Universitas Gadjah Mada, 2007)
This experiment was conducted to determine the effect of dietary single cell protein as substitution for fish meal in fish diets. Five isonitrogenous (38% crude protein) and isocaloric (3,040 kcal digestible energy/kg diet) practical diets, namely diets A, B, C, D and E with different levels of single cell protein were fed to juvenile common carp (Cyprinus carpio). Twenty juveniles/aquarium with an initial weight of 1.20±0.11 g per individual were used in this experiment. Fish were cultivated in aquarium of 60 l capacity under standardized conditions at 26±10 C. The aquaria assigned to 5 treatments were arranged in triplicates. Diet A contained low dosage of single cell protein (0 g /100 g diet), while diets B (9.8 g /100 g diet), C (19.5 g /100 g diet), D (29.3 g /100 g diet), and diet E (39.5 g /100 g diet ), combined respectively with 39.5 g fish meal/100 g diet (diet A), 29.3 g fish meal/100 g (diet B), 19.5 g fish meal/100 g diet (diet C), 9.8 g fish meal/100 g diet (diet D), and 0 g fish meal/100 g diet (diet E). Fish were fed ad satiation for 45 days using these diets. The dietary with different level of single cell protein affected growth rate and feed efficiency. Fish fed on diet 39.5 g fish meal/100 g (diet A) produced the highest growth rate (1.15±0.267%) and feed efficiency (61.68±9.89%). Growth rate and feed efficiency decreased synchronously with increases in single cell protein in the fish diets. Lysine and tryptophan were higher in single cell protein than in fish meal; whereas arginine, histidine, isoleucine, leucine, methionine, phenylalainine, threonine and valine were lower in single cell protein. On the other hand, fish fed on experimental diets did not show any significance differences in the survival rate.